2016
DOI: 10.1038/srep37354
|View full text |Cite
|
Sign up to set email alerts
|

Circulating long-non coding RNAs as biomarkers of left ventricular diastolic function and remodelling in patients with well-controlled type 2 diabetes

Abstract: Contractile dysfunction is underdiagnosed in early stages of diabetic cardiomyopathy. We evaluated the potential of circulating long non-coding RNAs (lncRNAs) as biomarkers of subclinical cardiac abnormalities in type 2 diabetes. Forty-eight men with well-controlled type 2 diabetes and 12 healthy age-matched volunteers were enrolled in the study. Left ventricular (LV) parameters were measured by magnetic resonance imaging. A panel of lncRNAs was quantified in serum by RT-qPCR. No differences in expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 44 publications
4
99
0
1
Order By: Relevance
“…Було досліджено, що LIPCAR може служити корисним раннім діагностичним інструментом для оцінки діастолічної функції ЛШ та ремоделювання [8,9]. Враховуючи раніше досліджувану асоціацію між параметрами діастолічної функції ЛШ та рівнями експресії LIPCAR, було висунуто гіпотезу, що циркулюючі рівні цих lncRNAs можуть бути потенційними біомаркерами діастолічного порушення функції ЛШ у пацієнтів з діабетом 2 типу, які показали більш високий рівень LIPCAR порівняно з пацієнтами з нормальною діастолічною функцією [10]. MIAT бере участь у патологічному ангіогенезі, тому пропонується як пре диктор інфаркту міокарда [11].…”
Section: Anyapol777@gmailcomunclassified
“…Було досліджено, що LIPCAR може служити корисним раннім діагностичним інструментом для оцінки діастолічної функції ЛШ та ремоделювання [8,9]. Враховуючи раніше досліджувану асоціацію між параметрами діастолічної функції ЛШ та рівнями експресії LIPCAR, було висунуто гіпотезу, що циркулюючі рівні цих lncRNAs можуть бути потенційними біомаркерами діастолічного порушення функції ЛШ у пацієнтів з діабетом 2 типу, які показали більш високий рівень LIPCAR порівняно з пацієнтами з нормальною діастолічною функцією [10]. MIAT бере участь у патологічному ангіогенезі, тому пропонується як пре диктор інфаркту міокарда [11].…”
Section: Anyapol777@gmailcomunclassified
“…Zhang's team study showed that by inhibiting lncRNA‐AK081284, interleukin‐17 ablation reduced cardiac interstitial fibrosis and improved cardiac function in diabetic mice . Gonzalo‐Calvo et al indicated that lncRNAs are independent predictors of diastolic function and remodelling in patients with type 2 diabetes . Accordingly, it is of great significance to study the regulation of lncRNA in DCM.…”
Section: Long Noncoding Rnasmentioning
confidence: 99%
“…4 Gonzalo-Calvo et al indicated that lncRNAs are independent predictors of diastolic function and remodelling in patients with type 2 diabetes. 70 Accordingly, it is of great significance to study the regulation of lncRNA in DCM.…”
Section: Long Noncoding Rnasmentioning
confidence: 99%
“…Recently, long non‐coding RNAs (LncRNA) of plasma, that were thought to promote cancer development, were found to take a significant role in diabetes 2 progression . Long non‐coding RNAs are non‐coding RNAs that are longer than 200 nucleotides, and many of them were demonstrated to play a pivotal role in the development and progression of many diseases including cancer .…”
Section: Introductionmentioning
confidence: 99%
“…MT‐LIPCAR (Mitochondrially Encoded Long Non‐Coding Cardiac Associated RNA) is an RNA gene and is affiliated with the non‐coding RNA class. Diseases associated with MT‐LIPCAR include congestive heart failure and myocardial infarction . GAS5 (growth arrest specific 5) is an RNA gene and is affiliated with the non‐coding RNA class.…”
Section: Introductionmentioning
confidence: 99%